2014
DOI: 10.9734/irjpac/2014/7645
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study of Benzamide Coordination with Zinc (II)

Abstract: Author UAK designed the study, performed the calculations and wrote the first draft. Author GSYA performed a part of calculations and helped to analyse the results. Authors AGK and ATKH helped to analyse the results. Author LAB allowed LaC The SMo (Laboratory of Theoretical Chemistry and Molecular Spectroscopy)research team to perform some calculations on the server of his laboratory. Author JBM is LaC The SMo Director; he managed this scientific work. All authors read and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Moreover, the potential metabolites of INER-1577 #3 and #4 produced in the liver and plasma were more hydrophilic and it was thus difficult for them to cross the blood-brain barrier (BBB) into the CNS for imaging. Because HDACs are zinc-centered metallo-enzymes [25], and the benzamide groups of the INER-1577 analogs compete with amino acids for coordination with zinc atoms [26], the function of the analogs is terminated after hydrolysis of the benzamide groups in the liver or blood. Although the researches indicated that benzamide derivatives showed anticancer activities under phase II clinical trials based on HDAC inhibition, there is no information available on its microsomal stability and metabolism for mocetinostat (MGCD0103) and no metabolites could be detected after incubation of MS-275 in human liver microsomes for entinostat (MS-275) [27].…”
Section: Identification Of Metabolites Of Iner-1577s In Biosystemsmentioning
confidence: 99%
“…Moreover, the potential metabolites of INER-1577 #3 and #4 produced in the liver and plasma were more hydrophilic and it was thus difficult for them to cross the blood-brain barrier (BBB) into the CNS for imaging. Because HDACs are zinc-centered metallo-enzymes [25], and the benzamide groups of the INER-1577 analogs compete with amino acids for coordination with zinc atoms [26], the function of the analogs is terminated after hydrolysis of the benzamide groups in the liver or blood. Although the researches indicated that benzamide derivatives showed anticancer activities under phase II clinical trials based on HDAC inhibition, there is no information available on its microsomal stability and metabolism for mocetinostat (MGCD0103) and no metabolites could be detected after incubation of MS-275 in human liver microsomes for entinostat (MS-275) [27].…”
Section: Identification Of Metabolites Of Iner-1577s In Biosystemsmentioning
confidence: 99%